Association of specific haplotypes of GAS6 gene with stroke - Muñoz, Xavier; Obach, Víctor; Hurtado, Begoña; de Frutos, Pablo García; Chamorro, Ángel; Sala, Núria (Thrombosis and Haemostasis, 2007)
The product of the growth arrest-specific gene 6 (GAS6),a ligand for tyrosine kinase receptors, is a vitamin K-dependent protein, structurally related to anticoagulant protein S. Gas6-deficient mice are protected against thrombosis, demonstrating the importance of this protein in the cardiovascular system. In a preliminary study on GAS6 polymorphisms and atherothrombotic disease we found an association between the AA genotype of the c.834+7G>A GAS6 polymorphism and stroke. In order to further explore this association by considering GAS6 haplotypes and the main stroke subtypes,457 patients with ischemic stroke, 199 with hemorrhagic stroke and 150 asymptomatic controls were genotyped for eight GAS6 polymorphisms and other genetic markers in the same genome region. Association was measured by logistic regression analysis.The THESIAS program was used to measure linkage disequilibrium and haplotype frequencies. In univariate analysis, the GAS6 c.834+7AA genotype was found associated with decreased risk for stroke (OR: 0.59; 95%CI: 0.37–0.93).After adjustment for vascular risk factors, association was maintained when stroke subtypes affecting the microvasculature such as lacunar stroke and deep haemorrhage, were grouped together (OR: 0.44; 95%CI: 0.21–0.90). Furthermore, haplotype analysis revealed that association was even stronger when the c.834+7A allele was present in a specific haplotype (CACA) of four GAS6 polymorphisms. From these results we conclude that the A allele of the GAS6 c.834+7G>A polymorphism and more specifically, the CACA haplotype, is less prevalent in patients with stroke, suggesting a protective role for stroke of this haplotype.
Keywords: GAS6; haplotypes; polymorphisms; stroke